Know more, spend more? The impact of financial literacy on household consumption - Milena Dinkova; Adriaan S. Kalwij; Rob Alessie (Utrecht University, Utrecht University School of Economics (U.S.E.), 2019)
This paper examines the relationship between household consumption and financial literacy for Dutch households. The economic framework is a simple life-cycle model of consumption in which financial literacy affects the rate of return on assets. The theoretical predictions are that financial literacy and consumption levels are positively correlated for plausible values of the intertemporal elasticity of substitution and that financial literacy and consumption growth are positively correlated. We use Dutch data from the LISS household panel to empirically test our theoretical predictions. Our results provide evidence for a strong positive association between couples' non-durable consumption and the level of the male partner's financial literacy. We did not find evidence for an association between consumption growth and financial literacy. Our results are robust to including household assets, interest in financial literacy and to examining different stages of the life-cycle.
Keywords: 330; life-cycle model; financial literacy; self-assessed financial literacy; household consumption